A Review on Touch-less Biometric Fingerprint Authentication - Chourasiya, Anushri; Pandey, Rakesh (International Journal of Computer Sciences and Engineering, 2025)
In recent years, there is new technique which has been introduced i.e. touch-less fingerprint authentication system which may replaces the biometric device or scanner which is considered as unhygienic as well as costly. As we know that authentication system possess by a combination of username and password and this combination may be hacked because anyone of your friends or relative may perform brute force attack by guessing your password which may related to your personal details. But fingerprint cannot be stolen or copied that is why fingerprint authentication is the best authentication system. Everyone has distinct fingerprint and no one can authenticate or unauthorized access without your existence. So, on having this feature biometric device or scanner has been introduced in past years and now it is to be replaced by the touch-less fingerprint authentication or recognition system. This recognition can be perform either by webcam or by hand held device i.e. mobile. The purpose of this paper is to review the existing touch-less fingerprint systems and how much they are reliable and effective as compare to their results.